Design optimization of a plasma gasification reactor utilizing computational numerical simulations - Castillo-Benavides, Alberto (2023)
The main objective was the development of an optimized municipal waste gasification reactor geometry utilizing plasma. Here, numerical simulation utilizing the COMSOL Multiphysics software was used to achieve an optimized bidimensional geometry. Initial conditions for the reactor were defined using the researchers’ experience. Then, 16 different combinations of four geometric parameters were set, where the gas chamber’s superior, and inferior radius, it’s length and lastly the fusing chamber volume were varied. Of these, two combinations that optimized the mixing of gases and heat exchange with the exterior were found. It was confirmed that these designs allowed for the proper melting and gasification of the theoretical waste. Further, the smelted material also possessed a viscosity lower than 10 Pa s needed to flow out of the reactor.